PROACTIVE STRATEGY AGAINST CORRUPTION: (A REVIEW OF THE MANAGEMENT OF PUKAT UGM YOGYAKARTA) - Sri Isnani Setiyaningsih; Ahmad Muthohar; Darul Qutni (Scholar Express Journals, 2023)
This research examines the system and management of anti-corruption monitoring implemented by PUKAT (Pusat Kajian Anti Korupsi) at Gadjah Mada University, Yogyakarta. PUKAT, as an anti-corruption organisation in higher education, has achieved remarkable success in monitoring court cases related to corruption and bribery. This study aims to assess the effectiveness of PUKAT's efforts and explore its impact on higher education and society. In the context of the pervasive problem of corruption in Indonesia, PUKAT's experience in controlling and monitoring judicial proceedings represents a proactive contribution to problem-solving at the state level. This research, which uses an ex post facto survey method coupled with in-depth interviews and observations, seeks to provide insights into PUKAT's system and management strategies
Keywords: Anti-Corruption Watch; System and Management against Corruption; Higher Education Contribution